Are Standard Follow-Up Parameters Sufficient to Protect Neurocognitive Functions in Patients with Diabetes Mellitus who Underwent Coronary Artery Bypass Grafting? - Sacli,Hakan (2020)
Abstract Objective: We aimed to compare the effectiveness of cognitive function protection between the standard follow-up parameters and advanced neuromonitoring methods in diabetic patients who underwent coronary artery bypass grafting during cardiopulmonary bypass. Methods: Study design was prospective and observational. Patients were separated into two groups, treated only with standard follow-up parameters (Group 1) and followed up with the change of regional cerebral tissue oxygenation (rSO2) by near-infrared spectroscopy (Group 2). Neurocognitive functions were evaluated preoperatively and postoperatively before discharge in all patients using the Montreal Cognitive Assessment (MoCA) test. Results: Cognitive functions of Group 2 patients in the postoperative period were significantly higher than Group 1 patients (P=0.001). The mean postoperative MoCA score of patients was significantly lower than the mean preoperative MoCA score in Group 1 (24.8±2.2 vs. 23.6±2.6, P=0.02). However, mild cognitive dysfunction was significantly lower in Group 2, compared to Group 1 (P=0.02). Conclusion: In patients followed up with standard parameters, a significant decrease in cognitive function was observed in the early period. However, the use of advanced neuromonitoring methods can significantly prevent this decrease in cognitive functions.